Implementation of U.K. Earth System Models for CMIP6. (1st April 2020) - Sellar, Alistair A.; Walton, Jeremy; Jones, Colin G.; Wood, Richard; Abraham, Nathan Luke; Andrejczuk, Miroslaw; Andrews, Martin B.; Andrews, Timothy; Archibald, Alex T.; de Mora, Lee; Dyson, Harold; Elkington, Mark; et al.
Abstract: We describe the scientific and technical implementation of two models for a core set of experiments contributing to the sixth phase of the Coupled Model Intercomparison Project (CMIP6). The models used are the physical atmosphere‐land‐ocean‐sea ice model HadGEM3‐GC3.1 and the Earth system model UKESM1 which adds a carbon‐nitrogen cycle and atmospheric chemistry to HadGEM3‐GC3.1. The model results are constrained by the external boundary conditions (forcing data) and initial conditions. We outline the scientific rationale and assumptions made in specifying these. Notable details of the implementation include an ozone redistribution scheme for prescribed ozone simulations (HadGEM3‐GC3.1) to avoid inconsistencies with the model's thermal tropopause, and land use change in dynamic vegetation simulations (UKESM1) whose influence will be subject to potential biases in the simulation of background natural vegetation. We discuss the implications of these decisions for interpretation of the simulation results. These simulations are expensive in terms of human and CPU resources and will underpin many further experiments; we describe some of the technical steps taken to ensure their scientific robustness and reproducibility. Plain Language Summary: Complex models of the Earth system are valuable tools for understanding the processes responsible for our changing climate. The Coupled Model Intercomparison Project (CMIP) is a well‐established activity of the World Climate Research Programme that brings together results from these models to better understand their process representation and to pool their projections for robust understanding of future climate pathways. The latest phase of CMIP (CMIP6) is larger and more ambitious than previous phases. We detail the setup of two U.K. models (HadGEM3‐GC3.1 and UKESM1) for a core set of experiments contributing to CMIP6, including simulations of historical and future periods covering 1850 to 2300. We highlight assumptions made in applying the prescribed CMIP6 input data to these models. We outline the technical steps to ensure the reproducibility of these simulations. Key Points: We describe the implementation of U.K. Earth system models for CMIP6 experiments We document the assumptions made in implementing the external forcing in line with experiment protocols Special attention was paid to ensuring that these expensive simulations were reproducible